UMP establishes strategic collaboration with Petronas Chemicals to stimulate innovation and productivity - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) recently signed a Memorandum of Understanding (MoU) with Petronas Chemicals MTBE Sdn. Bhd. (PCMTBE) to establish a strategic collaboration between the academic institution and industry player, in terms of sharing of technology and field expertise, as well as developments in human capital, academic and research.